PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN HASIL BELAJAR IPS DI MI AL ABAYYINAH - Mulyasari, Siti Artanti; Fahri, Muhammad; Yono (STKIP Al Islam Tunas Bangsa dan HEPI, 2024)
This research begins with the low social studies learning outcomes of class IV students at MI Al Bayyinah Dramaga, Bogor Regency, to obtain class IV social studies learning outcomes at MI Al Bayyinah Dramaga, Bogor Regency by using a contextual teaching and learning approach. From the data analyzed, this research uses a contextual teaching and learning approach using research instruments, namely observation, tests, syllabus, lesson plans, teacher observation sheets, student observation sheets, and documents. This research produces data on student learning outcomes in social studies subjects in class IV at MI Al Bayyinah Dramaga, Bogor Regency before the implementation of contextual teaching and learning, showing that around 68% of students scored below the KKM with an average of 47.69% compared to that set at MI which is 65. .00. There are 7 students who reach the KKM standard, while there are 19 students who have not reached the KKM standard. After implementing the contextual teaching and learning approach in cycle 1, all 26 students achieved the KKM with an average score of 90.38, the learning level/learning completeness was 100%. This proves that the application of the CTL (Contextual Teaching and Learning) approach can improve social studies learning outcomes for class IV students at MI Al Bayyinah Dramaga, Bogor Regency